3D morphometric evaluation of palatal rugae among Malaysian Malay population - Al-Selwi, Abdullah Abdulkhaleq Mohammed (2022)
Palatal rugae pattern may have a promising and interesting future for human identification purpose. Previous studies showed that palatal rugae pattern has a lot of morphological and dimensional characteristics that are different from a person to another even among the identical twins. In fact, palatal rugae are anatomically located in a well protected place, behind boons, teeth, cheeks and lips, which provides a good alternative option for human identification in mass disasters and accidents. This study aimed to evaluate the variability and uniqueness of palatal rugae among Malaysian Malays using 3D dental models. A 3D Next Engine Laser scanner (USA) was used to digitize plaster dental casts of 130 Malaysian Malay patients (65 males and 65 females) obtained from the archive of Orthodontic Clinic, Hospital Universiti Sains Malaysia. The resulting 3D models were highlighted using Paint 3D software (USA) for the purpose of rugae shape assessment. Rugae size category and direction were assessed using 3Matic research software (Belgium). The classification method of Thomas and Kotze (1983) as described by Kapali et al. (1997) was adopted. Palatal rugae uniqueness was performed by superimposing 42 pairs of digital models (21 models were duplicated from the same patients and 21 models were randomly selected from the group). The 42 superimposition sets were examined for palatal rugae surface fitting by a single blinded evaluator. Prevalence of palatal rugae was presented in percentages while mean and standard deviation were presented for number of rugae. Chi-square analyses were used to evaluate the association between sex and prevalence of palatal rugae variables. Independent t-test was used to compare sex difference in number of palatal rugae. Correct/wrong decision of superimposition was presented in percentages. P-value <0.05 was considered statistically significant. Total number of rugae was 1359 (673 in males and 686 in females). Wavy shape was the predominant rugae among the sample, followed by curve shape and straight shape respectively. The predominant rugae size category was the primary size. Forwardly directed rugae were the most prevalent rugae among the sample. There was no significant difference regarding rugae features between males and females except for the rugae direction in the left side of the palate, as the backward rugae direction was more prevalent among the females (p=0.001). Palatal rugae pattern was unique. No two individuals have the same pattern. Wavy shape, Primary size and forward direction were the most prevalent among Malaysian Malays. Palatal rugae is unique thus could be used for human identification in the case where pre-mortem and post-mortem records are available.